Qualidade do leite produzido nos meses de inverno e verão na região central do Rio Grande do Sul em diferentes níveis tecnológicos - Araujo, Fernando Oliveira de (2011)
With the objective to evaluate the effect of the level of specialization of dairy production units, what it results in more intense use, or not, production resources, on the quantiqualitative aspects of milk, an evaluation was conducted in dairy production units (UPL) in two mesoregions of the state of Rio Grande do Sul: West Central Mesoregion Rio-Grandense East Central Mesoregion Rio-Grandense. Milk samples were collected in forty property and analyzed the composition and quality of milk. The UPL were divided into two groups: Specialized System (ES) and Semi-Specialized System (SS). The classification of production systems was based on the genetic composition of the herd, milking system, equipment used for cooling milk, nutritional planning of the herd, use of pastures and fodder reserves, presence of technical assistance in the property and the level of importance of the dairy activity for the farmers. Were also collected data regarding the productivity of properties, such as stocking rate and milk production per hectare. Milk components (fat, protein, lactose and solids) were determined by Near-infrared spectroscopy (NIRS) and the somatic cell count and total bacterial count were realized by eletronic count flow cytometry. There were no significant differences in composition, milk quality and productivity between the producers of the ES in winter and summer. In the SS system only percentage of fat was difference during winter and summer. For other values there was no difference in the SS. When compared, the SS and SE systems differ in composition, quality and productivity. Compared with the SS, the milk produced in the SE had lower chemical composition, but with better microbiological quality and higher production volume.